DESTINATION BRANDING KAMPUNG WISATA SARUGO OLEH KELOMPOK SADAR WISATA DI KABUPATEN LIMA PULUH KOTA - Latifah Nur Aini; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Sarugo Tourism Village is one of the traditional tourist destinations in Lima Puluh Regency. Sarugo is an acronym for Saribu Rumah Gonjong. This destination consists of a collection of traditional houses surrounded by hills and rice fields. The hills are used as orange plantations by the community. The Tourism Awareness Group as the founder and manager continues to develop and market Sarugo Tourism Village to be known to the public. The purpose of this study was to determine the stages of destination branding carried out by the Tourism Awareness Group in developing and marketing the Sarugo Tourism Village. This study uses qualitative research methods with descriptive analysis. There were six subjects in this study, namely 2 people from the Tourism Awareness Group, 1 person from the Tourism Awareness Group supervisor, 1 person from the Tourism Office, and 2 visitors. The results of this study indicate that there are five stages of destination branding carried out by the Tourism Awareness Group, namely: Market Potential Mapping, Brand Identity Development, Brand Introducing, Participation of Involved Parties, Monitoring, Evaluation and Review. Keywords : Destination Branding, Komunikasi Pariwisata, Kampung Wisata Sarugo